The Village Headmaster - Okoro, Anezi (African Universities Press, 1967)
The Village Headmaster is the new broom at the village school.His efforts to 'sweep clean' meet opposition and disaster in this sequel to The Village School.
Keywords: Juvenile literature-English Language readers-Primary-Fiction-Nigeria (English)